2006
DOI: 10.1016/j.adolescence.2005.11.009
|View full text |Cite
|
Sign up to set email alerts
|

The antecedents and consequences of autonomous self‐regulation for college: A self‐determination theory perspective on socialization

Abstract: Using self-determination theory, two studies investigated the relations among perceived need support from parents, their adolescents' autonomous self-regulation for academics, and the adolescents' well-being. Study 1 indicated that perceived need support from parents independently predicted adolescents' wellbeing, although when mothers' and fathers' data were examined separately, the relation was stronger for mothers than for fathers. In Study 2, autonomous self-regulation for planning to attend college was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
191
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 286 publications
(227 citation statements)
references
References 31 publications
(38 reference statements)
15
191
0
7
Order By: Relevance
“…All seven items were scored on a 5-point Likert scale, ranging from 1 (strongly disagree) to 5 (strongly agree). Both the original English version and the Dutch version have adequate reliability and validity (e.g., Niemiec et al, 2006;Ryan & Frederick, 1997). Cronbach's alpha was .81 in our sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All seven items were scored on a 5-point Likert scale, ranging from 1 (strongly disagree) to 5 (strongly agree). Both the original English version and the Dutch version have adequate reliability and validity (e.g., Niemiec et al, 2006;Ryan & Frederick, 1997). Cronbach's alpha was .81 in our sample.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we assessed participants' subjective vitality using the Subjective Vitality Scale (Ryan & Frederick, 1997). A Dutch version of this questionnaire has been used by Niemiec et al (2006). A sample item reads as follows: "Currently, I feel so alive I just want to burst."…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has found the processes occurring internally as well as socially have affected individuals' phenomenological experiences and the internalization of attitudes, values, and regulatory processes (Niemiec et al, 2006). Therefore, an individual's decision to major in agricultural education could be influenced by how he or she was socialized.…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…The differing degree to which the individual has accepted values makes SDT different from other developmental theories. This perspective does not treat internalization as a dichotomous concept in which values are either accepted or not by the individual, but as a more complex construct in which different types of internalization can be distinguished depending on the type of inducement present (Niemiec et al, 2006).…”
Section: Recommendations For Further Researchmentioning
confidence: 99%
“…Subsequently, to evaluate the orientation of motivation a questionnaire was sent out by email to all participants (n ¼ 87). The questionnaire was based on a Dutch version of the Academic SelfRegulation Questionnaire (previously used in Niemiec et al 2006;Vansteenkiste et al 2009;Soenens 2012;Vansteenkiste et al 2012). We modified the Academic SelfRegulation Questionnaire for the purpose of this study: changed the present tenses into past tenses, replaced the words "parents, friends, teachers … ."…”
Section: Participantsmentioning
confidence: 99%